Grammatical Errors in Thesis Backgrounds Written by Students at the English Language Education Program of Universitas Negeri Padang - Azzuhudi, Muhammad Habib; Tiarina, Yuli (Journal of English Language Teaching, 2024)
Errors are common occurrence made by students when they are learning which In this case, students’ error in learning English. Error analysis is a methodology to find these errors. This study aimed to describe students’ errors in writing thesis backgrounds who took Paper Thesis Writing class in Universitas Negeri Padang. Descriptive research was implemented to this study using quantitative method. The population and sample of this research was K1-K5 2019 students. By using cluster random sampling to decide the sample, K1 was the chosen sample of this research. This study was conducted by using the 23 students’ final project in Paper Thesis Writing class which is thesis proposal backgrounds as the data. Students’ errors were classified into four types which was omission, addition, misformation and misordering. After analyzing the data, three out of four types of error were found in students’ thesis background. Among the total of 97 errors found, misformation had the highest occurrence of 62 errors, followed by addition with 18 errors, omission with 17 errors and no misordering error.